ANALISA LAPORAN PERTANGGUNGJAWABAN PUSAT BIAYA UNTUK MENILAI KINERJA MANAJER PUSAT PERTANGGUNG JAWABAN - Heru Harmadi Sudibyo (Universitas Nasional, 2017)
The purpose of this study is to determine the role and application of the cost center responsibility report as a measure of performance of central responsibility manager. Data used quantitative data. Sources of this research data using primary and secondary data in the form of financial statements. The method of analysis used is the method of variance, where the results obtained there are still costs that have been effective (favorable) and not yet effective (unfavorable). The results explain that the application of responsibility accounting at cost centers and investment centers has been quite good. However, performance appraisals at cost centers are quite efficient.